Peran Teknologi Blockchain dalam Meningkatkan Keandalan Akuntansi - Fitria Novi Nuraini (UNIVERSITAS MARITIM AMNI SEMARANG, 2025)
In an increasingly complex digital era, the demand for a transparent, reliable, and efficient accounting system is increasing. Conventional accounting systems still face various challenges, such as potential data manipulation, recording errors, and dependence on third parties for the verification process. Blockchain technology is present as a potential solution to strengthen the integrity and transparency of the accounting system through a decentralized and immutable ledger recording mechanism. This study aims to examine how blockchain can be applied in accounting systems and to what extent this technology is able to improve the reliability of accounting information. The method used is a literature review, by analyzing 20 scientific articles published between 2020 and 2025. The results of the study show that blockchain has great potential in increasing efficiency, reducing audit costs, and minimizing the risk of fraud and data manipulation. However, challenges such as implementation costs, scalability, and regulatory uncertainty are the main obstacles to its adoption. This study provides a deeper understanding of the opportunities and constraints of implementing blockchain in accounting, and opens up space for further research related to the integration of this technology into modern accounting practices.